Genomics insights into a Mycobacterium pinnipedii isolate causing tuberculosis in a captive South American sea lion (Otaria flavescens) from Italy - Alba, Patricia; Caprioli, Andrea; Cocumelli, Cristiano; Eleni, Claudia; Diaconu, Elena Lavinia; Donati, Valentina; Ianzano, Angela; Sorbara, Luigi; Stravino, Fiorentino; Cerini, Natalino; Boniotti, Maria Beatrice; Zanoni, Mariagrazia; et al. (Frontiers in Microbiology, 2023)
Tuberculosis (TB) affects humans and other animals and it is caused by bacteria within the Mycobacterium tuberculosis complex (MTBC). Here we report the characterization of a Mycobacterium pinnipedii that caused a TB case in a sea lion (Otaria flavescens) kept in an Italian zoo. The animal died due to severe progressive disorders involving respiratory and gastro-enteric systems, and the skin. At necropsy, typical gross lesions referable to a TB generalized form were found. In particular, nodular granulomatous lesions were detected in the lungs and several lymph nodes, and colonies referable to Mycobacterium spp. were isolated from lung, mesenteric and mediastinal lymph nodes. The isolate was identified by PCR as a MTBC, spoligotyped as SB 1480 ("seal lineage") and characterized by whole genome sequencing analysis confirming that the MTBC involved was M. pinnipedii. The analysis of the resistome and virulome indicated the presence of macrolide and aminoglycoside resistance genes intrinsic in M. tuberculosis (erm-37 and aac(2')-Ic), and confirmed the presence of the region of difference 1 (RD1), harbouring the esxA and esxB virulence genes, differently from its closest taxon M. microti. As for other MTCB members, M. pinnipedii infection can spill over into non-pinniped mammalian species, therefore zoological gardens, veterinary practitioners and public health officers should be aware of the hazard posed by tuberculosis from marine mammals. Since the isolate under study, as well as all available genomes of M. pinnipedii investigated in this study, retains almost all the M. tuberculosis virulence genes, it could indeed cause infection, lesions and disease also in other animal species, including humans.Tuberculosis (TB) affects humans and other animals and it is caused by bacteria within the Mycobacterium tuberculosis complex (MTBC). MTBC members belong to the family Mycobacteriaceae and are Gram-positive, acid-fast bacilli. The taxonomy of organisms in the MTBC is in constant evolution (World Organisation for Animal Health, 2022). Based on the current knowledge, the MTBC is comprised of nine human-adapted lineages (L), representing M. tuberculosis sensu stricto (L1-4 and L7-8) and M. africanum (L5-6 and L9), plus different animal-associated lineages including M.